Teachers' evaluation of supervisory classroom visitation program of Our Lady of Grace Academy, Caloocan City - Coruña, Maria Juanita J. (Animo Repository, 1977)
The study presents the teachers' evaluation of the Supervisory Classroom Visitation Program of Our Lady of Grace Academy as a means of improving instruction. The data used in this study were the mean responses of 21 high school teachers and 24 grade school teachers to the questionnaire made by this researcher about the classroom visitation program of Our Lady of Grace Academy. The said number of teachers represent the entire faculty members of both departments. Researcher used four categories to be evaluated by all the teachers. These four categories were purpose, design and practices, principal's competence, value of classroom visits and general impression. The ratings made by the teachers were tabulated and means were computed and finally analyzed in the context of the rating scale made by the researcher. The results show, in general, that teachers have a very good impression of the program and that they consider it a big help towards the improvement of their teaching. In the light of the findings, the following conclusions were made : 1) Teachers assess the purpose, design and practices of the program as effective. 2) Teachers assess the principal as very competent in carrying out the supervisory function of classroom visitation. 3) Teachers consider the program as a very effective means of improving instructions.